(untitled) (Fiep Bulletin - online, 2013)
This study aimed to monitor the loss of body weight (BW) of professional layers, before and after a charge of physical training and technical, determining the degree of dehydration(DD). It is a cross-sectional study, conducted in 2 days, evaluating 27 football players for a professional sports club in Belém-PA. In collects data was used to search a protocol that information was obtained for classifying the state of hydration of players. The evaluated had, on average, 24 years old, 1.78m tall and 74Kg of BW and most served as attacker(22.2%), driving(22.2%) or goalkeeper(14.8%). When evaluated, according to the state of hydration on the 1st day, the Maximum Temperature (MT) was 31.5°C and relative humidity (RH) of 87%, most athletes showed state of Ihydration (SIH)(89%) while the 2nd day, the MT was 31°C and 95% of RH, the majority of players showed state of Dehydration Dew (SDD)(55.6%). Moreover, both at 1 on the 2nd day of evaluation, athletes in SDD ingested, on average, a total water volume than the athletes in a state of SIH. It was observed that the average volume ingested Hydride (VIH) after training was significantly higher in both ratings ((607+141,2 and 785+156,2).When compared with the position of active, most of the players taken SIH served as attacker or steering wheel and that the majority SDD had served as goalkeeper. It follows that the DD among athletes may have been influenced by VIH, climatic factors and intensity of activity required in accordance with the active position. However, many times in the hydration drills/games is not prioritized, which contributes to the variation in the BW, increasing the DD and causing damage to health and sports performance.